Toward the mechanism of jarastatin (rJast) inhibition of the integrin αVβ3 - Vasconcelos, Ariana A.; Estrada, Jorge C.; Caruso, Icaro P. [UNESP]; Kurtenbach, Eleonora; Zingali, Russolina B.; Almeida, Fabio C.L. (Elsevier, 2024)
Disintegrins are a family of cysteine-rich small proteins that were first identified in snake venom. The high divergence of disintegrins gave rise to a plethora of functions, all related to the interaction with integrins. Disintegrins evolved to interact selectively with different integrins, eliciting many physiological outcomes and being promising candidates for the therapy of many pathologies. We used NMR to determine the structure and dynamics of the recombinant disintegrin jarastatin (rJast) and its interaction with the cancer-related integrin αVβ3. rJast displayed the canonical fold of a medium-sized disintegrin and showed complex dynamic in multiple timescales. We used NMR experiments to map the interaction of rJast with αVβ3, and molecular docking followed by molecular dynamics (MD) simulation to describe the first structural model of a disintegrin/integrin complex. We showed that not only the RGD loop participates in the interaction, but also the N-terminal domain. rJast plasticity was essential for the interaction with αVβ3 and correlated with the main modes of motion depicted in the MD trajectories. In summary, our study provides novel structural insights that enhance our comprehension of the mechanisms underlying disintegrin functionality.
Keywords: Disintegrin; Dynamics; Integrin; Jarastatin; Structure; αVβ3